Detection of cassava brown streak ipomoviruses in aphids collected from cassava plants - Nanyiti, Sarah; Kabaalu, Richard; Alicai, Titus; Abidrabo, Phillip; Seal, Susan E.; Bouvaine, Sophie; Bailey, Andy M.; Foster, Gary D. (Frontiers in Sustainable Food Systems, 2023)
Cassava is an important staple food in Africa and a major source of carbohydrates for 800 million people globally. However, cassava suffers severe yield losses caused by many factors including pests and diseases. A devastating disease of cassava is cassava brown streak disease (CBSD) caused by the cassava brown streak ipomoviruses (CBSIs) (family Potyviridae), Cassava brown streak virus (CBSV), and Ugandan cassava brown streak virus (UCBSV). Spread of CBSD is mainly through planting infected stem cuttings used for propagation. Transmission of CBSIs by the insect vector (Bemisia tabaci) has been reported. However, experimental transmission efficiencies of CBSIs are usually low. Recent research has showed the occurrence of a DAG motif associated with aphid transmission in other potyviruses, within the coat protein gene of CBSV. Consequently this study aimed to explore the possibility that besides whiteflies, aphids may transmit CBSIs. Cassava plants were assessed during a survey for occurrence of CBSD and aphids as potential alternative CBSIs vectors. We collected aphids from CBSD-symptomatic and symptomless cassava plants within farmers' fields in Uganda during April–July 2020. The aphids were analyzed for the presence of CBSIs by reverse transcriptase-polymerase chain reaction (RT-PCR) and to determine aphid species using mitochondrial cytochrome oxidase (mtCOI) barcoding. Unusual aphid infestation of cassava plants was observed at 35 locations in nine districts across Uganda and on 11 other plant species within or adjacent to cassava fields. This is the first report of aphids infesting cassava in Uganda. Molecular analysis of the aphid confirmed presence of three different aphid species in the surveyed cassava fields, namely, Aphis solanella, Aphis fabae mordvilkoi, and Rhopalosiphum sp. mtCOI nucleotide sequences for the aphids in which CBSIs were detected are deposited with Genbank under accession numbers OP223337-40. Both UCBSV and CBSV were detected by RT-PCR in aphids collected from cassava fields with CBSD-affected plants. The CBSIs were detected in 14 aphid samples collected from 19 CBSD-symptomatic cassava plants. These results suggest the ability of aphids to acquire CBSIs, but transmission experiments are required on their vector potential.